The Influence of Instagram Social Media Exposure, Product Quality, and Price Perception on Purchasing Decisions with Brand Image as an Intervening Variable (Study on the Instagram Account @handmadeshoessby) - Regita Octavia; Ida Bagus Cempena; Achmad Yanu Alif Fianto (International Journal of Economics, Business and Innovation Research, 2025)
The purpose of this study was to determine the effect of Instagram social media, product quality, price perception on purchasing decisions with brand image as an intervening variable. This study uses a quantitative approach, this research is included in causal quantitative research. The population in this study were followers of the @handmadeshhoessby Instragram account which amounted to 908,000 followers. Based on calculations, the sample in this study was rounded up to 400 followers of the @handmadeshhoessby Instragram account. The sampling technique in this study used probability sampling techniques. The results of this study are Instagram social media exposure has an effect on purchasing decisions, product quality has an effect on purchasing decisions, price perception has an effect on purchasing decisions, Instagram social media exposure has an effect on brand image, product quality has an effect on brand image, price perspective has an effect on brand image, brand image has an effect on purchasing decisions, brand image can mediate the effect of Instagram social media exposure on purchasing decisions, brand image can mediate the effect of product quality on purchasing decisions, brand image can mediate the effect of price perception on purchasing decisions.